2001
DOI: 10.1289/ehp.01109s2309
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory regeneration as a mechanism for renal tubule carcinogenesis of fumonisin B1 in the F344/N/Nctr BR rat.

Abstract: Fumonisin B1(FB1) is a fungal metabolite of Fusarium verticillioides (= F. moniliforme), a fungus that grows on many crops worldwide. Previous studies demonstrated that male BD IX rats consuming diets containing 50 ppm fumonisin B1 developed hepatocellular carcinomas. In our recent studies, diets containing FB1 at 50 ppm or higher concentrations induced renal tubule carcinomas in male F344/N/Nctr BR rats and hepatocellular carcinomas in female B6C3F1/Nctr BR mice. The carcinogenicity of FB1 in rats and mice is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…FB 1 (Gelderblom et al 1992;Howard et al 2001) and PA (Dickens and Jones 1961;Palmgren and Ciegler 1983) were also found to be carcinogenic mycotoxins and may interact with OTA, which is a potent carcinogen. Moreover, FB 1 was found to have a pronounced nephrotoxic effect on animal kidneys Bucci et al 1998), which can be additive to the nephrotoxic effect of OTA.…”
Section: Discussionmentioning
confidence: 99%
“…FB 1 (Gelderblom et al 1992;Howard et al 2001) and PA (Dickens and Jones 1961;Palmgren and Ciegler 1983) were also found to be carcinogenic mycotoxins and may interact with OTA, which is a potent carcinogen. Moreover, FB 1 was found to have a pronounced nephrotoxic effect on animal kidneys Bucci et al 1998), which can be additive to the nephrotoxic effect of OTA.…”
Section: Discussionmentioning
confidence: 99%
“…Toxins produced by F . verticillioides such as fumonisin B 1 can be detected in plant tissues (especially in kernels) with and without symptoms, and are harmful to humans and animals (Marasas et al ., ; Howard et al ., ). This fungal pathogen primarily penetrates seeds and then moves to the root, mesocotyl and crown, and ultimately to the kernels (Munkvold et al ., ; Murillo‐Williams & Munkvold, ).…”
Section: Introductionmentioning
confidence: 97%
“…Fusarium verticillioides (teleomorph Gibberella fujikuroi (synonym, Gibberella fujikuroi)) is a widely distributed plant pathogen that causes many important diseases of corn including seedling blight, root rot, stalk rot, and kernel or ear rot (Foley, 1962;Kommedahl & Windels, 1981). Toxins produced by F. verticillioides such as fumonisin B 1 can be detected in plant tissues (especially in kernels) with and without symptoms, and are harmful to humans and animals (Marasas et al, 1984;Howard et al, 2001). This fungal pathogen primarily penetrates seeds and then moves to the root, mesocotyl and crown, and ultimately to the kernels (Munkvold et al, 1997;Murillo-Williams & Munkvold, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…FB1 [114,115] and PA [73,74] were also found to be carcinogenic mycotoxins and may interact in this dimension with OTA, which is also proven carcinogen [76,116,117,118]. Moreover, FB1 was found to have a pronounced nephrotoxic effect on animal kidneys [61,119], which can be additive to nephrotoxic effect of OTA.…”
Section: The Joint Mycotoxin Interaction and The Complex Etiology mentioning
confidence: 99%